Experimental investigation of the effect of hydrogen addition on the sooting limit and structure of methane/air laminar counterflow diffusion flames. (15th September 2022) - Khare, R.; Vlavakis, P.; Langenthal, T. Von; Loukou, A.; Khosravi, M.; Kramer, U.; Trimis, D.
Abstract: The influence of hydrogen ( H 2 ) addition on the sooting limit and structure of methane/air laminar counterflow diffusion flames has been studied. Soot limits have been obtained using the laser light scattering technique for CH 4 / H 2 mixtures with H 2 concentration varying from 0–20% by volume in the fuel mixture for different strain rates. The resulting soot limit map shows a significant increase in the fuel concentration at the soot limit with increasing amounts of H 2 . To understand this trend, temperature and species concentration profiles have been measured and compared under the influence of H 2 addition in (a) an incipiently sooting and (b) in a sooting CH 4 /air flame. Flame temperatures have been measured using a thin-wire S-type thermocouple and species profiles have been measured using the gas chromatography technique (GC). The results indicate a significant decrease in the amounts of higher hydrocarbons such as benzene and naphthalene (which are considered important soot precursors) with an increase in H 2 concentration for the sooting flame. To explain this decrease in the concentration of higher hydrocarbons, pathway analysis has been performed to elucidate the influence of H 2 on the formation and consumption of soot forming species. Highlights: Addition of hydrogen to methane counterflow flames reduces its soot formation tendency. Hydrogen addition leads to increase in temperature of methane flames. Except acetylene concentration of soot precursors such as ethylene, benzene, naphthalene etc. decreases. Decrease in the amount of soot precursors leads to a decrease in the soot formation.